Get set for English literature - Robinson, Christine (Get Set for University : GSU, 2022)
The English Language volume assumes no prior knowledge of the subject. For students who have never studied English Language before, it will give an idea of what to expect. For students already studying English Language at school, it will provide a concise but comprehensive learning aid.Part One covers core subjects taught in the first year of most English Language degrees. Topics include: phonetics and phonology; vocabulary; inflectional morphology; syntax; the history of English; regional and social variation; language change; and language and poetry. Part Two tackles the study skills needed at university level and discusses issues such as lectures, tutorials and seminars; writing skills; essays and dissertations; and examinations. Learning tools include a sample degree exam paper and a sample essay answer